Atmospheric CO2 Sequestration in Seawater Enhanced by Molluscan Shell Powders - Namikawa, Yuto; Suzuki, Michio (Environmental Science & Technology, 2024)
Carbon capture, utilization, and storage (CCUS) are widely recognized as a promising technology for mitigating climate change. CO2 mineralization using Ca-rich fluids and high-concentration CO2 gas has been studied extensively. However, few studies have reported CO2 mineralization with atmospheric CO2, owing to the difficulty associated with its low concentration. In seawater, the biomineralization process promotes Ca accumulation and CaCO3 precipitation, assisted by specific organic matter. In this study, we examined the conversion of atmospheric CO2 into CaCO3 in seawater using shell powders (Pinctada fucata, Haliotis discus, Crassostrea gigas, Mizuhopecten yessoensis, Turbo sazae, and Saxidomus purpurata). Among the six species, the shell powder of S. purpurata showed the highest rate of CaCO3 formation and recovery of CaCO3. NaClO treatment test revealed that the organic matter in the shells enhanced the CO2 mineralization. All materials used in this study, including atmospheric CO2, seawater, and shells, are economically feasible for large-scale applications. Using shell powder for CO2 mineralization in seawater embodies an innovative technological advancement to address climate change.